An Absent Presence: Visitor Narratives of Journeys and Support for Prisoners During Imprisonment. Issue 1 (17th November 2015) - HOLLIGAN, CHRIS
Abstract: The system of allocation of prisoners to prisons in Scotland results in the incarceration of prisoners at significant distance from their homes, creating an obstacle to the maintenance of family ties. Using unpublished statistical and primary research data collected with visitors of prisoners during 2014, this qualitative study reports an examination of peregrinations designed to provide prisoner support. More specifically, it converges upon perceptions of why, in the minds of visitors, these journeys are consequential for sustaining the welfare of their loved ones, and notes that prison authorities over‐represent visitation as a panacea for alleviating the pains of imprisonment.